Synthesis of nanostructured gadolinium doped mixed ferrite: A novel catalyst for the mineralization of textile dyes. Issue 12 (15th June 2023) - Kousar, Tehmina; Katubi, Khadijah Mohammedsaleh; Zulfiqar, Sonia; Alrowaili, Z.A.; Ansari, Mohd Zahid; Al-Buriahi, M.S.; Aadil, Muhammad; Hassan, Warda; Mahmood, Farzana; Hussain, Mehtab
Abstract: Herein, cobalt-nickel mixed ferrite (Co0 · 5 Ni0 · 5 Fe2 O4, CNFO) and gadolinium doped cobalt-nickel mixed ferrite (Co0 · 5 Ni0.5 Gd0.1 Fe1 · 9 O4, G-CNFO) materials have been synthesized at the nanoscale via the microemulsion technique. The physicochemical features of the CNFO and G-CNFO materials were examined by advanced structural (PXRD and FTIR), morphological (FESEM), elemental (EDX), and optical (UV/Vis and transient photocurrent) studies. Under visible light, the catalytic activity of CNFO and G-CNFO materials was compared using Congo red and Aniline blue dyes as model textile pollutants. The G-CNFO material showed better photocatalytic activity than CNFO material, as it eliminated almost 21% more dye than CNFO material under the same experimental conditions. In order to find the optimal parameter for the experiments, the variables affecting the catalytic properties of the G-CNFO material were investigated in considerable detail. These variables included pH, catalyst dosage, dye concentration, temperature, and irradiation time. Scavenging and transient photocurrent experiments were also carried out in order to determine the key reactive oxygen species and the formation of electron-hole pairs. The G-CNFO mineralized the Congo red dye almost three times faster than its counterpart and showed a negligible loss in its catalytic activity even after five successive catalytic cycles. The combined effects of the G-CNFO material's tuned band structure, high light harvesting abilities, reduced electron-hole recombination, and nanostructured morphology resulted in its enhanced photocatalytic activity.